(untitled) (Padmakanya Journal of Science and Technology, 2025)
The use of facemask as a protection measures against the dust and communicable diseases has been a common practice. Surgical mask, in particular provide some form of protection against these threats. However, if used improperly or reused, these masks could become carriers of diseases, counteracting their protective measures. The relation of the mask use frequency and extent of microbial contamination has not been properly explored. This study aims to determine the bacterial and fungal profile, bacterial load and assess the antimicrobial susceptibility of bacteria isolated from the one day and three day used mask. The research was conducted from December 2023 to August 2024 at the Microbiology Laboratory of Padmakanya Multiple Campus. Samples from the inner surface of surgical masks were processed using serial dilution on Plate Count Agar (PCA) for bacterial counts by the spread plate technique, and incubated at 37ºC for 24 hours. Fungi were cultured on Potato Dextrose Agar (PDA) at 25ºC for 5 days. Additional media such as Mannitol Salt Agar, Blood Agar, Chocolate Agar, M-Endo Agar, and Cetrimide Agar were used for bacterial and fungal analysis. Out of 20 masks used for one day, no fungal growth was detected, and 45% (9 masks) showed the presence of Staphylococcus spp., and no bacteria were found on the remaining masks. In contrast, 20 facemasks reused for three days yielded 22 bacterial isolates. The predominant bacterial species was Staphylococcus aureus (14 isolates, 63.64%), and the most frequent fungal species was Aspergillus spp. (12 isolates, 60%). Compared to one-day used masks, the three-day reused masks showed a higher microbial load and diversity. Notably, all S. aureus (100%) were methicillin –resistant (MRSA) and showed resistant to multiple β-lactam antibiotics including Penicillin-G, Oxacillin, and Amoxicillin. Gram-negative isolates, however, remained largely sensitive to tested antibiotics. The study highlights increased microbial contamination with prolonged facemask reuse, underscoring the importance of timely replacement and proper mask hygiene to prevent potential health risks.